Assessing behavioral and psychological symptoms of dementia: a comprehensive review of current options and future perspectives - Pozzi, Federico Emanuele; Calì, Luisa; Ferrarese, Carlo; Appollonio, Ildebrando; Tremolizzo, Lucio (Frontiers in Dementia, 2023)
The behavioral and psychological symptoms of dementia (BPSD) are a heterogeneous set of challenging disturbances of behavior, mood, perception, and thought that occur in almost all patients with dementia. A huge number of instruments have been developed to assess BPSD in different populations and settings. Although some of these tools are more widely used than others, no single instrument can be considered totally satisfactory, and each of them has pros and cons. In this narrative review, we will provide a comprehensive overview of the characteristics of a large number of such instruments, addressing their applicability, strengths, and limitations. These depend on the setting, required expertise, and people involved, and all these factors need to be taken into account when choosing the most suitable scale or tool. We will also briefly discuss the use of objective biomarkers of BPSD. Finally, we will try to provide indications for future research in the field and suggest the ideal characteristics of a new possible tool. This should be short, easy to understand and use, and treatment-oriented, providing the clinicians with data such as frequency, severity, and triggers of behaviors, allowing them to find appropriate strategies to effectively tackle BPSD.